ChemInform Abstract: Synthetic Strategies for the Preparation of Butenolides and Their Transformation into Other Derivatives. Issue 17 (April 2016) - Barbosa, Luiz C. A.; Teixeira, Robson R.; Amarante, Giovanni W.
Abstract: Review: 160 refs.